2018
DOI: 10.21037/tlcr.2018.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Small cell lung cancer tumors and preclinical models display heterogeneity of neuroendocrine phenotypes

Abstract: Background: Small cell lung cancer (SCLC) is a deadly, high grade neuroendocrine (NE) tumor without recognized morphologic heterogeneity. However, over 30 years ago we described a SCLC subtype with "variant" morphology which did not express some NE markers and exhibited more aggressive growth. Methods:To quantitate NE properties of SCLCs, we developed a 50-gene expression-based NE score that could be applied to human SCLC tumors and cell lines, and genetically engineered mouse (GEM) models. We identified high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
264
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(291 citation statements)
references
References 70 publications
27
264
0
Order By: Relevance
“…Next, we compared in situ the quantitative and qualitative extent of the immunological microenvironment of SCLC tumors according to NE-low and NE-high subtypes. In line with previously published in vitro data, our results confirm that NE-low tumors are significantly more infiltrated by immune cells, primarily by CD8+ effector T cells (Zhang et al, 2018).…”
Section: I and J)supporting
confidence: 92%
See 1 more Smart Citation
“…Next, we compared in situ the quantitative and qualitative extent of the immunological microenvironment of SCLC tumors according to NE-low and NE-high subtypes. In line with previously published in vitro data, our results confirm that NE-low tumors are significantly more infiltrated by immune cells, primarily by CD8+ effector T cells (Zhang et al, 2018).…”
Section: I and J)supporting
confidence: 92%
“…Our group on the same TMA sets clustered NE-high and NE-low SCLC subsets (Lohinai et al, 2020) based on the top RNA genes associated with NE differentiation (Gazdar 2018;Zhang et al, 2018). Furthermore, the latest preclinical studies suggest that, compared to the NE-high, the NE-low subtype is more likely to respond to immunotherapy due to its 'immune oasis' phenotype, emphasizing the necessity and importance of molecular and in situ immunological characterization before the assessment of therapies to this type of recalcitrant cancer (Gazdar 2018;Zhang et al, 2018;Ito et al, 2016).…”
Section: I and J)mentioning
confidence: 99%
“…On the other hand, a negative correlation was observed between Lac/Glc and ssGSEA scores derived from gene sets related to neuronal processes, which tend to be expressed in cell lines with neuroendocrine differentiation (lonescu et al, 2007). We therefore derived neuroendocrine scores for our cell lines based on a 50-gene signature (Zhang et al, 2018) and found that cell lines with high neuroendocrine scores are invariably low in Lac/Glc ( Figure 1F ). Altogether these data indicate that hypoxia gene sets correlate with glycolytic metabolism even when cells are cultured in normoxia, and that cell lines with neuroendocrine-like gene expression signatures release relatively little lactate per glucose consumed.…”
Section: Resultsmentioning
confidence: 99%
“…Distinguishing SCLC subtypes by expression of neuroendocrine genes such as CHGA and GRP identifies two groups: neuroendocrine high (NE high ; ∼80%) and neuroendocrine low (NE low ; ∼20%). Within the NE high group, the basic helix-loop-helix (bHLH) transcription factor ASCL1 is considered a master regulator for a majority of these SCLC, while a related bHLH factor, NEUROD1, characterizes a smaller subset with intermediate neuroendocrine characteristics (Osborne et al 2013;George et al 2015;Borromeo et al 2016;Zhang et al 2018). In contrast, most NE low SCLCs do not express ASCL1 or NEUROD1.…”
mentioning
confidence: 99%